Effect of Fungicides on Germination and Survival of Pine Seedlings Chir (Pinus Roxburghii Sargent) - Chandra, J. P.; Sharma, R. K. (Indian Forester, 1975)
A study to control damping-off in Chir pine (Pinus roxburghii) seedings, caused by Fusarium spp. was conducted at Solan (India) by using 11 treatments comprising of drenching the Soil and Seed with different concentrations of five fungicides, namely, Mercuric chloride, Brassicol, Captan, Thiram and Dithane M 45. The results, show that none of treatments had any significant effect on germinations of the seed. The drenching of soil with 0.3% Captan solution, or 0.25%. Thiram solutions, or 0.2% Dithane M 45 solution gave significantly better survival of seedlings than other treatments, there being no significant difference in between these three treatments.